Cleaning efficacy of EDDY versus ultrasonically-activated irrigation in root canals: a systematic review and meta-analysis - Xiaojun Chu; Shuting Feng; Weiqing Zhou; Shuaimei Xu; Xiongqun Zeng (BMC, 2023)
Abstract Background Ultrasonically-activated irrigation (UAI) is effective in root canal irrigation but may damage canal walls. EDDY is a sonic activation system with flexible working tips that cause no harm to dentinal walls. This review explores the intracanal cleaning efficacy of EDDY compared with UAI in vitro. Methods The systematic review was registered in the PROSPERO database (CRD42021235826). A literature search was conducted in six electronic databases. In vitro studies that compared the removal of smear layer, debris, soft tissue or microbes in root canals between EDDY and UAI were included. Data extraction and quality assessment were performed. Meta-analyses were conducted on smear layer removal and debris elimination with the standardized mean difference (SMD). Heterogeneity was measured using the I2 test and the Chi2 test. The random-effect model was used when I2 > 50%, or p < 0.1, otherwise the fixed-effect model was applied. The level of significance was set at p < 0.05. Results 19 articles were included in this systematic review and 7 articles were included in meta-analyses. Meta-analyses on smear layer removal showed unimportant differences between EDDY and UAI at any canal third (coronal [SMD = 0.08, 95% confidence interval (95%CI): -0.29 to 0.45; p = 0.44, I2 = 0%]; middle [SMD = 0.02, 95% CI: -0.44 to 0.47; p = 0.94, I2 = 0%]; apical [SMD = 0.01, 95%CI: -0.35 to 0.38; p = 0.70, I2 = 0%]). Meta-analyses on debris removal evaluated by scanning electron microscope (coronal [SMD = 0.03, 95% CI: -0.41 to 0.46; p = 0.27, I2 = 23%]; middle [SMD = -0.24, 95% CI: -0.83 to 0.35; p = 0.80, I2 = 0%]; apical [SMD = 0.24, 95%CI: -0.20 to 0.67; p = 0.36, I2 = 2%]) and micro-CT (SMD = 0.36, 95% CI: -0.67 to 1.40; p = 0.03, I2 = 70%) both found insignificant differences. No meta-analysis was undertaken on soft-tissue removal and disinfection due to the various study designs, but the qualitative analyses implied that EDDY achieved similar performance to UAI in both aspects. Conclusions Limited evidence indicated that EDDY was comparable to UAI in removing smear layer, debris, soft tissue and microbes ex vivo. Considering UAI may damage canal walls, EDDY might be a substitute for UAI in irrigation activation. But more randomized clinical trials are required to explore the clinical extrapolation of the results in this review.